2021
DOI: 10.1136/bmjgh-2020-004595
|View full text |Cite
|
Sign up to set email alerts
|

Institutional mistrust and child vaccination coverage in Africa

Abstract: IntroductionDespite considerable improvements in vaccination coverage over the last decade, half of the world’s unvaccinated and undervaccinated children are located in Africa. The role of institutional trust in explaining vaccination gaps has been highlighted in several qualitative reports but so far has only been quantified in a small number of high-income countries.MethodsWe matched information on child vaccination status from the Demographic Health Surveys with information on institutional trust from the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…For example, more skeptical individuals toward the government or those dissatisfied with its crisis management may be more reluctant to accept a state-provided vaccine. [20,21] We only have data on trust in the government's crisis management in Malawi and satisfaction in Mali and Nigeria but find our hypotheses are confirmed in bivariate logistic regressions (Table A.6). However, after controlling for all other factors in Table 1, the coefficients are no longer significant.…”
Section: Correlates Of Hesitancymentioning
confidence: 75%
“…For example, more skeptical individuals toward the government or those dissatisfied with its crisis management may be more reluctant to accept a state-provided vaccine. [20,21] We only have data on trust in the government's crisis management in Malawi and satisfaction in Mali and Nigeria but find our hypotheses are confirmed in bivariate logistic regressions (Table A.6). However, after controlling for all other factors in Table 1, the coefficients are no longer significant.…”
Section: Correlates Of Hesitancymentioning
confidence: 75%
“…For example, more skeptical individuals toward the government or those dissatisfied with its crisis management may be more reluctant to accept a state-provided vaccine. [20,21] We only have data on trust in the government's crisis management in Malawi and satisfaction in Mali and Nigeria but find our hypotheses confirmed in bivariate logistic regressions (Table A.6). However, after controlling for all other factors in Table 1, coefficients are no longer significant.…”
Section: Correlates Of Hesitancymentioning
confidence: 80%
“…Vaccination uptake in Africa is associated with the level of trust communities have for government. For example, one study of child vaccination rates in Africa found a significantly reduced rate of vaccination in regions where the local population was distrustful of local authorities, with a one standard deviation increase in the institutional mistrust index being associated with a 10% increase in the likelihood that a child had missed any of the eight basic vaccines [ 42 ].…”
Section: Discussionmentioning
confidence: 99%